Analisa Kekuatan Tarik Komposit Serat Pelepah Pisang Sebagai Alternatif Untuk Laminasi Kapal Ikan - ahmad mu'aazar habibie habibie; Akhmad Basuki widodo akhmad basuki widodo (Jurnal Jaring SainTek, 2022)
Fishing boats are vessels that almost 90% of the building materials are made of wood. The nature of wood that is easily weathered and attacked by wood destroying organisms causes fishing vessels with wood materials to be easily damaged. Banana trees are plants that thrive in Indonesia. In addition to the fruit, banana tree leaves are the part that is often used for reprocessing. However, the midrib of the tree cannot be utilized optimally and will become unused waste. Therefore, the author has an innovation using banana midrib fiber as a composite material as a wood ship lamination material. Therefore, researchers need to do a test, namely by tensile test of variations in fiber thickness of 1 layer, 2 layers, 3 layers on a banana midrib fiber composite and polyester resin to measure the tensile strength value of the composite which refers to the ASTM 638-02a standard. Keywords : Wooden ship, banana fiber, Composite